2006
DOI: 10.5194/angeo-24-1305-2006
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of 150-km echoes over Jicamarca based on low-power VHF observations

Abstract: Abstract. In this work we summarize the statistics of the socalled 150-km echoes obtained with a low-power VHF radar operation at the Jicamarca Radio Observatory (11.97 • S, 76.87 • W, and 1.3 • dip angle at 150-km altitude) in Peru. Our results are based on almost four years of observations between August 2001 and July 2005 (approximately 150 days per year). The majority of the observations have been conducted between 08:00 and 17:00 LT. We present the statistics of occurrence of the echoes for each of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 18 publications
7
53
2
Order By: Relevance
“…Their results indicate a high occurrence (>70 %) of echoes for all seasons but with slightly higher occurrence (>85 %) during June Solstice months. Chau and Kudeki (2006) results challenge the hypothesis of Tsunoda and Ecklund (2004) about the control of E s layers over the occurrence of 150-km echoes since off-equatorial E s layers occur more frequently during the December solstice in the Peruvian sector. Statistics of the occurrence of off-equatorial 150-km echoes in the Indian sector were also presented by Patra and Rao (2007).…”
Section: Observations and Analysiscontrasting
confidence: 52%
See 2 more Smart Citations
“…Their results indicate a high occurrence (>70 %) of echoes for all seasons but with slightly higher occurrence (>85 %) during June Solstice months. Chau and Kudeki (2006) results challenge the hypothesis of Tsunoda and Ecklund (2004) about the control of E s layers over the occurrence of 150-km echoes since off-equatorial E s layers occur more frequently during the December solstice in the Peruvian sector. Statistics of the occurrence of off-equatorial 150-km echoes in the Indian sector were also presented by Patra and Rao (2007).…”
Section: Observations and Analysiscontrasting
confidence: 52%
“…Because of the similarity with the seasonal variation of sporadic E layers (E s ) in that longitude sector, they suggested that the ionospheric irregularities causing 150-km echoes could be created by an off-equator E s instability (Cosgrove and Tsunoda, 2002). Using observations made by the JULIA (Jicamarca Unattended Long-term Investigations of the Ionosphere and Atmosphere) mode of the Jicamarca radar, Chau and Kudeki (2006) South American) sector. They found that 150-km echoes are observed virtually every day over Jicamarca.…”
Section: Observations and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…JULIA (Jicamarca Unattended Long-term Investigations of the Ionosphere and Atmosphere) uses a coherent scatter radar to accurately measure the drift velocities of plasma irregularities near 150 km altitude [Chau and Kudeki, 2006]. We convert these drift velocities to electric field values using the IGRF and compare the eastward electric field component with simultaneous IVM measurements during C/NOFS overflights of Jicamarca.…”
Section: Comparison With C/nofsmentioning
confidence: 99%
“…This electric field is a fundamental parameter in any model describing equatorial ionospheric electrodynamics. However, direct measurements of the EEF have been restricted to a very few ground-based radars [Chau and Kudeki, 2006] and a small number of satellite missions [Fejer et al, 2008; de la Beaujardière and the C/NOFS Science Definition Team, 2004].…”
Section: Introductionmentioning
confidence: 99%